Participation of Learning Storytelling in Communication Ban Thademee Ching Karn District Loei Province for Support Tourism Skywalk Loei - Yoskhamlue, Kanlaya (Journal of Thammawat, 2022)
The purposes of academic research were to study 1) making stories about the quality of community life Ban Thademee Ching karn District Loei Province 2) storytelling multiple intelligence learning Ban Thademee Ban Thademee. There was cooperative action research. The taget group 50 leaders and citizen in Ban Thademee. The instrument were interview and participation on storytelling multiple intelligence learning. The data were analyzed by frequency and descriptive storytelling multiple intelligence learning. The findings : (1) Thequality of life community Thademee from the verbal telling of the impoverished 100 household. Total population of 367 households, population of 1,089 people, male 515 and female574. There are plain and mountain areas in total 4,000 rai. Is an agricultural area of 2,500 rai. The people were agriculture such as growing rice, vegetables, fruits, handicrafts, weaving.They was wicker and betel plate processing herbs for consumption and distributionto tourists who come to pay homage to the Big Buddha and Skywalk. (2) Storytelling multipleintelligence learning Ban Thademee Ban Thademee Gardner principle informal Thai Loei language and verbal usage patterns. There was content synthesized from a group process from creativity related to the way of life Ban Thademee beliefs and traditions. Learning to adapt to changes for the development of community tourism by reflecting the results of the information and stories in the media, brochures and videos.